534 PROGNOSTIC IMPACT OF CONTRAST-INDUCED ACUTE KIDNEY INJURY IN OLDEST OLD STEMI PATIENTS: A MULTICENTER REGISTRY. (15th December 2022) - Ruzzarin, Alessandro; Muraglia, Simone; Zilio, Filippo; Unterhuber, Matthias; Baessato, Francesca; Zanon, Sofia; Flaim, Massimo; Oberhollenzer, Rainer; Bonmassari, Roberto; Donazzan, Luca
Abstract: Introduction: Contrast-induced acute kidney injury (CI-AKI) is a well-known complication of ST-elevation acute myocardial infarction (STEMI) with an adverse impact on prognosis. Elderly patients are at higher risk for cardiovascular events. Moreover, renal function decreases with age. We sought to evaluate the incidence of CI-AKI in very elderly STEMI patients undergoing primary PCI (pPCI) and its impact upon outcomes in these patients. Methods: We retrospectively evaluated all very elderly patients (i.e. age above 85 years) treated with pPCI for STEMI in two hub-centers between January 2010 and June 2021. We defined CI-AKI as a rise in serum creatinine of ≥0.30 mg/dL over baseline during the first 48h from procedure. Follow-up data were determined from local clinical records during a twelve-months period. Results: Among 451 patients referred for STEMI at our institutions, 404 patients underwent pPCI. Overall, the incidence of CI-AKI was 16.3%. There was no significant age difference between CI-AKI and non CI-AKI groups (89.3 ± 2.9 vs 88.6 ± 2.7, p=0.11). Baseline features were similar except for higher prevalence of diabetes mellitus (31.1% vs 18.7%, p=0.03) and chronic kidney disease (CKD) (77% vs 25.7%, p< 0.01) in CI-AKI vs non CI-AKI group. CKD appeared to be strongly associated to higher risk of CI-AKI (OR 9.69, 95% CI: 5.0–18.5; p<0.01). Time-to-first composite MACE (all cause death, stroke, heart failure hospitalization) tended to be shorter without a significant difference between CI-AKI vs non CI-AKI group (252.3 vs 296.2 days, p=0.06) at one year follow-up, Conclusions: Underlying CKD is strongly associated with CI-AKI in oldest-old STEMI patients. CI-AKI group had a nonsignificant trend toward a reduction in time-to-first MACE.